(3PQjYI GdhUhd Edi EbJHGS RHO GdCUhds - (3GdGTNQ , eMeO Hf CHj HcQ, LeGd GdOjf,J (B991 (3g` s ((3YHO GdMejO Hf YHO GdLHGQ Hf eMeO GdeLGgO s)
(3ChdgG (B:s
(3CMeO ef MeOi dg ef fYeg eSJeWQkG HGdMeO ajV cQeg s
(3BNQgG (B:s
(3hGdGd hGdUMH fLhe GdXde gOGJfG Edi GdSHjd GdCbhe JeJ HMeO Gddg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B59 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B106s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg GdTjN eMeO YHO GdLdjd GdZRi GdNGUg HRHjO s
Keywords: (3Gdabg GdESdGejs